Slide member and manufacturing method thereof

JP7630265B2Active Publication Date: 2025-02-17DAIDO METAL IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020204629
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-09
Publication Date
2025-02-17
Estimated Expiration
2040-12-09

Smart Images

  • Figure 0007630265000004
    Figure 0007630265000004
  • Figure 0007630265000005
    Figure 0007630265000005
  • Figure 0007630265000006
    Figure 0007630265000006
Patent Text Reader

Abstract

To improve the compatibility of a soft metal layer of a slide member while maintaining the fatigue resistance of it.SOLUTION: The inventive slide member has a soft metal layer with laminated soft metal crystals. When the soft metal layer is divided into 5 equal parts in the thickness direction to form virtual divided areas, the average grain size of crystal particles present in a first divided area including the surface of the soft metal layer is equal to or lower than 2 / 3 of the average grain size of crystal particles present in the other 2-5 divided areas.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an improvement in a slide member and a manufacturing method thereof. [Background technology]

[0002] A sliding member generally comprises a base layer and a surface layer, and the surface layer supports a sliding member. The surface layer may be entirely or partially formed by plating using a soft metal material. In such a sliding member, Patent Document 1 proposes a material for forming the soft metal layer in which crystal grains of a soft material having a crystal grain size of 0.1 μm to 1 μm are aggregated into a mass shape. A plating layer having fine crystal grains is also disclosed in Patent Document 2. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. WO2017 / 094094 [Patent Document 2] JP 2003-156045 A Summary of the Invention [Problem to be solved by the invention]

[0004] As disclosed in Patent Document 1, when a plating layer having relatively fine crystal grains is used as a soft metal layer, when its surface is used as a sliding surface, the coating strength is improved and high fatigue resistance is provided due to the Hall-Petch relationship. In recent years, due to growing environmental awareness and legal regulations, automobile engines have been developed to be more fuel-efficient, with hybrid systems, idling stop systems, and lighter engines through downsizing. Downsizing of engines using turbochargers reduces the size of the engine while maintaining the same power performance as conventional engines, and the shaft diameter and metal width are reduced. As a result, bearings for automobile engines tend to be used in harsher environments than before, such as higher loads than before, and there is a demand for improved fit while maintaining fatigue resistance. When the soft metal layer described in Patent Document 1 is used, fatigue resistance is ensured, but the hardness of the soft metal layer itself increases as the crystal grains become finer, which may result in insufficient conformability. [Means for solving the problem]

[0005] The present invention is intended to solve the above-mentioned problems, and a first aspect of the present invention is defined as follows. A sliding member having a soft metal layer formed by laminating soft metal crystals, A sliding member, in which, when the soft metal layer is divided into five equal parts in the thickness direction to form virtual divided regions, the average crystal grain size of crystal grains present in a first divided region including the surface of the soft metal layer is 2 / 3 or less of the average crystal grain size of crystal grains present in the other second to fifth divided regions.

[0006] FIG. 1(A) shows a schematic diagram of the surface portion of the soft metal layer of the sliding member of the first aspect thus defined. In FIG. 1(A), the symbol S indicates a layer of relatively fine crystal particles constituting the first divided region on the surface side, and the symbol L indicates a layer of relatively large crystal particles constituting the second divided region and below. When a load indicated by the downward arrow is applied to the surface of the soft metal layer as shown in the left diagram of FIG. 1(A), the load is absorbed by the deformation of the layer L of relatively large crystal particles. That is, conformability is ensured (see the right diagram of FIG. 1(A)). On the other hand, since the surface of the soft metal layer is composed of the layer S of relatively fine crystal particles, cracks are unlikely to occur even when a large load is applied. That is, it has high fatigue resistance.

[0007] Fig. 1(B) shows a schematic diagram of a soft metal layer that is entirely made up of relatively fine crystal grains. In this example, fatigue resistance is ensured, but deformation is difficult when a load is applied, and it is difficult to obtain sufficient conformability. On the other hand, Figure 1(C) shows a schematic diagram of a soft metal layer that is entirely composed of relatively large crystal grains. In this example, the layer deforms significantly when a load is applied, ensuring conformability, but cracks are likely to occur, as shown in the diagram on the right.

[0008] As shown in FIG. 1(A), fatigue resistance is ensured in the surface layer of the soft metal layer, which is made up of relatively fine crystal grains, and conformability is ensured in the deeper layer of the soft metal layer, which is made up of relatively large crystal grains. When the soft metal layer is divided into five equal parts in the thickness direction, the first layer on the surface side is the only region made up of relatively fine crystal grains, while the remaining four regions are made up of relatively large crystal grains. In this way, conformability can be ensured by ensuring a sufficient thickness for the region made up of relatively large crystal grains.

[0009] In the soft metal layer, the average crystal grain size of the crystal grains present in the first divided region on the surface layer side is 2 / 3 or less of the average crystal grain size of the crystal grains present in the second to fifth divided regions on the deeper layer side. By providing such a difference in the distribution of crystal grain sizes between the surface layer side and the deeper layer side in the soft metal layer, the soft metal layer can have a good balance between fatigue resistance and conformability. If the ratio of the grain sizes between the two exceeds 2 / 3, fatigue resistance and / or conformability may decrease. For example, in one embodiment where the ratio exceeds 2 / 3, if the average grain size of the grains constituting the deep layer becomes small, the deep layer in the soft metal layer becomes difficult to deform, and conformability decreases. Here, the grain size is obtained by image processing of a vertical cross section of the surface of the soft metal layer using a sectioning method. In the sectioning method, the grain size of the grains is measured by dividing the length of a circle formed on the observation image by the number of grains passing through the circle. In the present invention, the grain size is calculated from the length of a circle with a diameter of 2 μm.

[0010] A second aspect of the present invention is defined as follows: in the slide member defined in the first aspect, the soft metal is one or more selected from bismuth (Bi), lead (Pb), indium (In), tin (Sn) and antimony (Sb), or an alloy thereof. The soft metals listed in the second aspect are industrially suitable for forming the soft metal layer of the slide member. Among these, it is preferable to select bismuth or an alloy thereof as the soft metal (third aspect) in order to reduce the environmental load.

[0011] A fourth aspect of the present invention is defined as follows: That is, in the slide member defined in any one of the first to third aspects, a resin layer is further laminated on the soft metal layer. According to the slide member of the third aspect thus defined, even when the resin layer is laminated on the surface of the soft metal layer, the soft metal layer can be ensured to have sufficient fatigue resistance while also having suitable conformability thereto.

[0012] A fifth aspect of the present invention is defined as follows. A method for producing a slide member having a soft metal layer, comprising the steps of: forming a precursor layer by depositing crystals of a soft metal on a surface of a substrate; a crystal refinement step of modifying the crystals constituting the surface of the precursor layer to refine the crystals, The method for manufacturing a slide member, wherein in the refinement step, when the precursor layer is divided into five equal parts in the thickness direction to form virtual divided regions, the average crystal grain size of crystal grains present in a first divided region including the surface of the precursor layer is set to 2 / 3 or less of the average crystal grain size of crystal grains present in the other second to fifth divided regions. The slide member manufactured by the method for manufacturing a slide member according to the fifth aspect thus defined exhibits the same effects as the slide member according to the first aspect.

[0013] The sixth aspect of the present invention is defined as follows: In the method for producing a slide member according to the fifth aspect, the soft metal is one or more selected from bismuth (Bi), lead (Pb), indium (In), tin (Sn), and antimony (Sb), or an alloy thereof. In the manufacturing method defined in the sixth aspect thus defined, an industrially suitable material is selected as the soft metal, so that the sliding member can be manufactured stably and inexpensively. It is even more preferable to select bismuth or an alloy thereof as the soft metal (seventh aspect).

[0014] The eighth aspect of the present invention is defined as follows: In the method for producing a slide member according to any one of the fifth to seventh aspects, a resin layer is further laminated on the soft metal layer. By selecting the resin constituting the resin layer, it is possible to improve properties such as seizure resistance.

[0015] A ninth aspect of the present invention is defined as follows: In the method for producing a slide member as defined in any one of the fourth to eighth aspects, the crystal refinement step is performed by negative pressure absorption blasting. By adopting a negative pressure absorption type blast in the crystal refinement step, the process is simplified and the size of the coarse crystals can be easily adjusted. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic diagram showing the function of the structure of the soft metal layer of the slide member of the present invention. [Diagram 2] FIG. 2 is a sectional view showing the configuration of a sliding member according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing a cross section of a soft metal layer, for explaining how to determine the average crystal grain size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will be described in further detail below based on the embodiments. The substrate layer constituting the sliding member is generally made of a metal material. In a bearing, which is an example of a sliding member, the substrate layer is configured by laminating a copper-based bearing alloy layer onto a backing layer made of steel, and an intermediate layer made of Ag, Ni, etc. may be formed on the bearing alloy layer. A soft metal layer is laminated on the base layer. Generally, this soft metal layer is formed by plating, but is not limited to plating. As the soft metal, one or more selected from indium (In), tin (Sn), lead (Pb), bismuth (Bi) and antimony (Sb), or alloys thereof can be used. Among them, it is preferable to adopt bismuth or an alloy thereof. As the plating method, wet electrolytic plating can be used, but this does not preclude the use of other plating methods.

[0018] When a base layer is plated with these soft metals, the crystals constituting the formed plating layer fall within a predetermined range in size. In the present invention, a layer formed by plating and not subjected to the crystal refinement treatment described later is called a precursor layer. The crystal grain size of the soft metal crystals constituting the precursor layer can be set to 0.3 to 1.5 μm. The crystal grain size was obtained by image processing of a vertical cross section of the precursor layer and then by a sectioning method. By adjusting the plating conditions, the crystal structure constituting the precursor layer becomes columnar, with the long axis of the columnar crystal being perpendicular to the surface of the precursor layer.

[0019] When the surface of the precursor layer was subjected to negative pressure absorption blasting, the crystal grains constituting the layer on the surface side of the precursor layer were selectively refined (crystal refinement treatment). Hereinafter, in this specification, the crystal grains refined in this way may be referred to as fine grains. The grain size of the fine crystals is smaller than the grain size of the crystals constituting the precursor layer.

[0020] The fine crystals were obtained by applying negative pressure absorption blasting to the surface of the plated precursor layer. When the precursor layer is subjected to a general blasting process, the crystals of the precursor layer are refined overall. The shot material and shot pressure used in the negative pressure absorption blasting can be selected arbitrarily according to the material of the precursor layer.

[0021] For example, the shot material may be alumina, glass beads, or other general-purpose shot materials, and the size of the shot material may be of a general purpose type. The shot pressure is appropriately adjusted depending on the selected precursor layer material and the material and size of the shot material.

[0022] In the above process, a soft metal layer (precursor layer) composed entirely of crystal grains of approximately uniform size was obtained by plating, and then a negative pressure absorption blasting process was carried out to selectively refine the crystal grains that make up the layer on the surface side. In addition, layers with different crystal grain sizes can be formed in the soft metal layer by changing the plating conditions in multiple stages. For example, plating is performed under the first condition from the fifth divided region to the second divided region to form a region (the second to fifth divided regions) made of relatively large crystal grains, and then, using the same plating material, the plating conditions are adjusted to form another region (the first divided region) made of relatively fine crystal grains on the first divided region. By using this method, the thickness of the region (the first divided region) made of relatively fine crystal grains that ensures fatigue resistance in the surface layer and the region (the second to fifth divided regions) made of relatively large crystal grains that ensures conformability deeper therein can be freely controlled. It is also possible to form three or more regions with different crystal grain sizes in the thickness direction of the soft metal layer. EXAMPLES

[0023] An embodiment of the present invention will now be described. The sliding member 1 of the embodiment had a cross-sectional structure shown in Fig. 2, for example. More specifically, a bimetal was manufactured by lining a steel backing layer 3 with a copper-based bearing alloy layer 4, and this bimetal was molded into a semi-cylindrical or cylindrical shape. Thereafter, the surface of the bearing alloy layer 4 was finished by boring. This resulted in the formation of a base layer 2 (thickness: 1.5 mm). Next, the surface of the semi-cylindrical or cylindrical molded product was cleaned (electrolytic degreasing + acid cleaning). The upper surface of the base layer 2 thus obtained was subjected to wet plating to form a plating layer (about 15 μm).

[0024] The plating conditions for forming the plating layer in this embodiment are as follows: <Plating conditions for Example 1 and Comparative Examples 1 and 2> A general plating solution was selected for bismuth plating (bismuth oxide: 10-70g / l, methanesulfonic acid: 30-150ml / l, additives: 20-60ml / l). The plating conditions were current density: 1-6A / dm 2 The plating bath temperature was 20 to 40°C. <Plating conditions for Comparative Example 3> Comparative Example 3 is bismuth-copper alloy plating. The plating solution used is bismuth oxide: 20-40 g / l, methanesulfonic acid: 30-70 ml / l, additives: 20-60 ml / l, and basic carbonic acid of 0.5-5 g / l. The current density is 3-4 A / dm 2 The plating bath temperature was 20 to 40°C. Those skilled in the art will understand that these plating conditions are not fixed, but are appropriately selected based on the experience of the plating operator.

[0025] The plating layer thus obtained was cleaned by a known method, and in Example 1, negative pressure absorption blasting was carried out. The conditions for the negative pressure suction blasting were as follows: For the cylindrical specimen, the blower frequency and circle feeder frequency were controlled to set the differential pressure at -0.05 to -0.02 MPa. Brown fused alumina #1000 was used as the blasting powder, and negative pressure suction blasting was performed on the inner surface of the specimen (the surface of the soft metal layer). In negative pressure suction blasting, the blasting powder collides with the surface of the plating layer (precursor layer) while rotating inside the cylindrical specimen. In other words, the blasting powder collides with the surface of the precursor layer at an angle, not perpendicularly. As a result, the energy of the blasting powder is concentrated on the surface side of the precursor layer, refining only the crystal particles on the surface side, and the crystal refining effect does not extend to the deeper layers of the precursor layer away from the surface.

[0026] In Comparative Example 2, a plating layer obtained in the same manner was subjected to a general-purpose shot blasting treatment. The conditions for the shot blasting treatment were as follows: For the semi-cylindrical sample, the ejection pressure was 0.15 MPa, and the blast powder was brown fused alumina #800. In this shot blasting, the blast powder collides perpendicularly with the surface of the plating layer (precursor layer). As a result, all the crystal grains that make up the precursor layer are refined. In other words, the crystals are refined not only in the crystal grains on the surface layer, but also in the deep layers below.

[0027] The properties of each sample obtained are shown in Table 1. [Table 1] In Table 1, the average crystal grain size of the crystal grains in each divided region was obtained as follows. The sample is cut in the axial direction and the cut surface obtained is observed. There are no particular limitations on the observation method, but for example, SIM (scanning ion microscope), SEM (scanning electron microscope), and EBSD (electron backscatter diffraction) can be used. The size of the field of view is not particularly limited as long as it includes the entire film thickness of the soft metal material layer.

[0028] In the observed cross section, as shown in FIG. 3, five points are taken evenly spaced in the film thickness direction of the soft metal material layer, and a circle with a radius of 1 μm is drawn from the center of each point. The number of crystal grains that this circle crosses is defined as n. Here, the grain size D is D=6.28 / n (μm) This process is performed for at least five rows, and the average crystal grain sizes D1 to D5 (the average crystal grain size D1 refers to the average of crystal grain sizes D1-1, D1-2, D1-3, ...) are calculated. Here, D1 represents the average crystal grain size present in the first divided region, which is located on the most surface side, and D2 to D5 are the average crystal grain sizes present in the second to fifth divided regions.

[0029] In Table 1, the results of the compatibility test were evaluated as follows. The sliding members of the examples and the comparative examples were brought into sliding contact with a rotating shaft, and foreign matter was successively added to the lubricating oil supplied to the sliding contact portion, and the time until seizure occurred was observed. If no seizure occurred even after 40 minutes or more, it was judged as clear. The test conditions for the conformability test are shown in Table 2. [Table 2]

[0030] In Table 1, the results of the fatigue resistance test were evaluated as follows. After repeatedly applying a load from the radial direction to a cylindrical sliding member (bearing) into which a rotating shaft is fitted, the surface of the soft metal layer of the sliding member sample is observed. Areas on the surface that have cracks are fatigued areas. The surface of the soft metal layer of the sliding member was photographed, the resulting image was processed, and the area ratio of the cracked parts to the entire surface was calculated. The obtained area ratio was regarded as the fatigue area ratio, and a fatigue area ratio of 20% or less was deemed to have passed the test.

[0031] The test conditions are as shown in Table 3. [Table 3]

[0032] The results in Table 1 show that only Example 1, in which the average crystal grain size ratio A / B was 57%, passed the conformability test and the fatigue resistance test. From this result, it is considered preferable that the average crystal grain size ratio is 2 / 3 (=66%) or less.

[0033] The present invention is not limited to the above-mentioned embodiment. Various modifications within the scope of the claims and within the scope of those skilled in the art are also included in the present invention. A device using a bearing mechanism, such as an internal combustion engine, using the sliding member of the present invention exhibits excellent sliding characteristics. [Explanation of symbols]

[0034] 1 Sliding member 2 Base material layer 3. Backing layer 4 Bearing alloy layer 5 Soft metal layer

Claims

1. A sliding member having a soft metal layer formed by laminating soft metal crystals, when the soft metal layer is divided into five equal parts in the thickness direction to form virtual divided regions, the average crystal grain size of crystal grains present in a first divided region including a surface of the soft metal layer is 2 / 3 or less of the average crystal grain size of crystal grains present in the other second to fifth divided regions, The second to fifth divided regions are more easily deformed than the first divided region.

2. 2. The sliding member according to claim 1, wherein the soft metal is one or more selected from the group consisting of bismuth (Bi), lead (Pb), indium (In), tin (Sn) and antimony (Sb), or an alloy thereof.

3. 2. The sliding member according to claim 1, wherein the soft metal is bismuth or a bismuth alloy.

4. 4. The sliding member according to claim 1, further comprising a resin layer laminated on the soft metal layer.

5. A method for producing a slide member having a soft metal layer, comprising the steps of: forming a precursor layer by depositing crystals of a soft metal on a surface of a substrate; a crystal refinement step of modifying the crystals constituting the surface of the precursor layer to refine the crystals, In the refinement step, blast powder is collided with the surface of the precursor layer at an angle rather than perpendicularly, and when the precursor layer is divided into five equal parts in the thickness direction to form virtual divided regions, the average crystal grain size of crystal grains present in a first divided region including the surface of the precursor layer is made less than 2 / 3 of the average crystal grain size of crystal grains present in the other second to fifth divided regions.

6. The manufacturing method according to claim 5, wherein the soft metal is one or more selected from the group consisting of bismuth (Bi), lead (Pb), indium (In), tin (Sn), and antimony (Sb), or an alloy thereof.

7. The method of claim 5, wherein the soft metal is bismuth or a bismuth alloy.

8. The method according to any one of claims 5 to 7, further comprising laminating a resin layer on the soft metal layer.

9. The method according to any one of claims 5 to 8, wherein the grain refinement step is performed by negative pressure suction blasting.

Citation Information

Patent Citations

  • Sliding member

    JP2003156045A

  • Method for preventing gray coating in hot-dip galvanization

    JP2008297625A

  • Cutting tool

    JP2013188842A

  • PROCESS OF MANUFACTURE OF SLIDE BEARING AND Sn GROUP OVERLAY OF SLIDE BEARING

    JP2014081040A

  • Sliding engine component

    US20160333489A1